1998
DOI: 10.1038/sj.jhh.1000680
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of Tamm–Horsfall protein in normotensive and hypertensive elderly patients

Abstract: Tamm-Horsfall protein (THP) is a glycoprotein that is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Patients with more tubular atrophy and interstitial fibrosis had lower urinary uromodulin levels. Uromodulin excretion also seems to increase gradually from birth to adulthood, becomes stable [24], [25], [26], [27] and then begins to decline after 60 years of age [28], [29]. We did not indentify an association between age and urinary uromodulin levels, probably due to narrow range of ages in this cohort.…”
Section: Discussionmentioning
confidence: 71%
“…Patients with more tubular atrophy and interstitial fibrosis had lower urinary uromodulin levels. Uromodulin excretion also seems to increase gradually from birth to adulthood, becomes stable [24], [25], [26], [27] and then begins to decline after 60 years of age [28], [29]. We did not indentify an association between age and urinary uromodulin levels, probably due to narrow range of ages in this cohort.…”
Section: Discussionmentioning
confidence: 71%
“…In previous small studies, urinary uromodulin levels were found to be decreased in older subjects and in subjects with renal impairment [19], [20]. In renal disease patients, uromodulin excretion was reduced in proportion to the extent of renal damage, and was a marker of distal tubular sodium reabsorption, but in these studies, the effects of BP on uromodulin were inconsistent [21], [22]. The TAL, where UMOD is selectively expressed is also the site where mutations of tubular transporters have resulted in rare Mendelian high or low BP syndromes [23].…”
Section: Discussionmentioning
confidence: 93%
“…Urinary uromodulin excretion increases from birth to adulthood and then remains stable until a decline after 60 years of age, 19,20 whereas the urinary uromodulin/creatinine ratio seems to be relatively stable from 4 years of age through the seventh decade of life. It is positively correlated with estimated glomerular filtration rate (eGFR), urine volume, dietary salt, and protein intake.…”
Section: Uromodulin Pathophysiologymentioning
confidence: 99%